Mortality for sarcoidosis patients on the transplant wait list in the Lung Allocation Score era: Experience from a high volume center. (October 2019) - Gangemi, Andrew J.; Myers, Catherine N.; Zheng, Matthew; Brown, James; Butler-LeBair, Marianne; Cordova, Francis; Marchetti, Nathaniel; Criner, Gerard J.; Gupta, Rohit; Mamary, A. James
Abstract: Rationale: Sarcoidosis progresses to end stage fibrotic lung disease in 10% of patients and may necessitate lung transplantation. Organ allocation is currently determined by the Lung Allocation Score (LAS), but its performance in a sarcoidosis population has not been evaluated. Objectives: To determine sarcoidosis-specific wait list mortality and identify predictive factors of death on the transplantation wait list. Methods: This was a single-center retrospective study of all sarcoidosis patients listed for lung transplant from March 2012 to February 2019. We compared patients who were transplanted to those who died awaiting organs. We collected baseline listing characteristics, physiologic testing, and outcomes data. Statistical analysis was performed by 2-tailed Student's t-test, Mann-Whitney U test, and Chi-Square analysis (where appropriate). Receiver-operating characteristic curves were constructed for variables reaching statistical significance. Results: Twenty eight sarcoidosis patients were included in analysis. Mortality among wait listed patients was 18%, which exceeded the mortality of COPD and IPF. LAS scores did not differ at initial listing (41 vs. 46, p = 0.35) or at transplant/death (41 vs. 41, p = 0.91); wait list times also did not statistically differ (307 days vs. 177 days, p = 0.19). We identified bilirubin (AUC = 0.92), DLCO (AUC = 0.84), FEV1/FVC at transplant/death (AUC = 0.85), and composite physiologic index (AUC = 0.86) as predictors of death on the transplant list. Pulmonary hypertension was not associated with death. Conclusion: Unexpected sudden death was common in our cohort and was associated with markers of advanced fibrotic disease, not pulmonary hypertension. Highlights: Mortality for sarcoidosis exceeded those of COPD and IPF. The Lung Allocation Score did not predict death on the transplant wait list. Markers of advanced fibrotic lung disease predicted death on the wait list. Occult cardiac sarcoidosis could not be excluded in most deaths.